A trace for the next generation : young Black theorists confronting transnational racism - McLoyd, Chike (Contemporary perspectives in race and ethnic relations., 2021)
"Based on eighteen months of ethnographic research in a high school E.L.L. classroom, this study contributes to the fields of new literacies studies and critical pedagogy by showing how transnational Black youth theorize and negotiate intersections of racism, justice, and education. Drawing on a multidimensional approach for understanding how racism is reproduced and resisted across various domains of power, the author shows how two young men from Haiti theorize the U.N. and INGO occupation of post-earthquake Haiti; a disjuncture between how Africa and Haiti are (mis)known in the U.S. and students' lived realities in their respective countries of origin; and finally, students' analysis of structural racism in the U.S. through a Justice for Trayvon unit that was co-taught from March-May 2012, when Trayvon Martin, George Zimmerman, and Stand Your Ground became household names. The author concludes by suggesting that we move toward a "lessons against white supremacies" framework for critical pedagogy. This framework draws on centering counter- narratives and thinking through the notion of de-colonial love to reframe everyday classroom praxis. Culturally informed, antiracist pedagogies must begin with students' theoretical work and experiential knowledge. Such an approach transforms classrooms into spaces for students to not only interrogate racism but also create (counter)texts that represent their subjectivities as young Black people in the 21st century"--